2019
DOI: 10.1093/ofid/ofz162
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Yield of a Molecular Diagnostic Panel for Enteric Pathogens in Adult Outpatients With Diarrhea and Validation of Guidelines-Based Criteria for Testing

Abstract: Background Molecular diagnostic panels for enteric pathogens offer increased sensitivity and reduced turnaround time. However, many pathogen detections do not change clinical management, and the cost is substantial. Methods We performed a retrospective chart review of adult outpatients with diarrhea at the University of Virginia who had samples tested by the FilmArray Gastrointestinal Panel (BioFire Diagnostics, Salt Lake City, UT) to identify the clinical yield and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…This study shows that the Novodiag Bacterial GEϩ kit has excellent analytical performance to detect bacterial enteropathogens in stools. This new kit showed better sensitivity than culture in accordance with the literature on syndromic molecular diagnosis (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). This gain of sensitivity allowed the detection of 2 Shigella sp./EIEC and 2 C. jejuni from patients with negative culture but suggestive symptoms.…”
Section: Discussionsupporting
confidence: 72%
“…This study shows that the Novodiag Bacterial GEϩ kit has excellent analytical performance to detect bacterial enteropathogens in stools. This new kit showed better sensitivity than culture in accordance with the literature on syndromic molecular diagnosis (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). This gain of sensitivity allowed the detection of 2 Shigella sp./EIEC and 2 C. jejuni from patients with negative culture but suggestive symptoms.…”
Section: Discussionsupporting
confidence: 72%
“…Our findings are consistent with those of a previous report of outpatients with diarrhea, where over 30% of orders for comprehensive testing did not meet the testing criteria established in the 2017 IDSA guidelines, 10 and over 20% of immunocompetent patients received antibiotics for pathogens that did not merit therapy. 8 …”
Section: Discussionmentioning
confidence: 99%
“…4 Comprehensive gastrointestinal (GI) PCR testing has been associated with decreased imaging, endoscopy, and antibiotic use, [5][6][7] but the optimal use of this assay remains unclear in the outpatient setting. 8 Patients may be tested for CDI with specific or comprehensive assays, but there is no guidance for which test to use and how to consider the pretest probability of alternate enteropathogens. To inform future interventions aimed at optimizing the use of these assays, we described their use among immunocompetent patients with and without CDI risk factors across different outpatient and nonmedically acute inpatient settings.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation into the underlying mechanisms revealed that psychological factors prior to infection and the severity of TD symptoms (rather than immunological or gene expression differences) were associated with the development of PI-AC. Additional research is necessary to better understand the role of TD in the development of PIIBS and other PI-AC, as well as to explore potential interventions to mitigate these effects [82].…”
Section: Post-infectious Chronic Gastrointestinal Disordersmentioning
confidence: 99%